Filling gaps in the knowledge of Goniodorididae taxa (Mollusca, Gastropoda, Nudibranchia) with description of seven new species - Paz-Sedano, Sofia; Cobb, Gary; Gosliner, Terrence M.; Pola, Marta (Zootaxa, 2024)
Goniodorididae H. Adams & A. Adams, 1854 is a family of small nudibranchs within the heterobranch mollusks. They are distributed throughout the world, and its large species richness makes it the most diverse family within superfamily Onchidoridoidea. Recently, several integrative taxonomic works have been focused on the study of Goniodorididae genera, applying different tools of morphological and molecular analysis. As a result, dozens of species belonging to the family have been described. However, the results of the most complete phylogenetic analyses carried out to date have shown that the species richness remains highly underestimated. In the present work we studied nine species of Goniodorididae from the Indo-Pacific and Atlantic Oceans that had been previously elucidated from molecular analyses. Morphological and anatomical analyses were carried out to describe or redescribe these species. The internal anatomy of the specimens was studied by dissections. As a result, seven new species from Australia, the Philippines, Singapore and Hawaii are described, Trapania franae sp. nov., Bermudella lahainensis sp. nov., Ceratodoris trypomandyas sp. nov., Murphydoris polkadotsa sp. nov., Naisdoris aurornata sp. nov., Naisdoris labalsaensis sp. nov. and Naisdoris vitiligata sp. nov. The species Bermudella mica (Ortea & Moro, 2014) and Ceratodoris plebeia (Bergh, 1902) are redescribed.